Colposcopy at a turning point - Kyehyun Nam (Korean Society of Obstetrics and Gynecology, 2018)
For women who have abnormal Pap test results, the biopsy under colposcopic evaluation is the gold standard for determining the treatment modality. To increase the effectiveness of colposcopic communication, the International Federation for Cervical Pathology and Colposcopy (IFCPC) recently published fourth new nomenclature, aiming to create an evidence-based terminology. To increase the diagnostic accuracy of colposcopy, multiple biopsies of two or more sites are recommended. Recently, with the introduction of human papillomavirus (HPV) vaccine for cervical cancer prevention, pre-cancerous diseases caused by virus types 16 and 18 have been reduced, which is expected to reduce the number of colposcopic examinations and make colposcopic diagnosis more difficult.